New Trends in Digital Data Storage for the Internet of Things - Saxena, A; Sharma, S; Dangi, S; Sharma, A; Patel, C (International Journal of Computer Sciences and Engineering, 2025)
As we know in every era, we need knowledge for performing the efficient job. That knowledge comes from past experiences & information, if we don’t have proper storage for information then that information will go in vain after few days. Today we have a large amount of data for storing, for which we used a different type of devices. Based on our need we have developed a different type of technologies to store the data such as Cds, DVDs, Floppy Disk, Hard Disks, Flash drive. As we know that technology is moving towards IoT and experts believe that IoT will consist 30 billion devices by 2020. So the physical world has more direct involvement in the computer world. Now our devices become intelligent systems that can share and analyze data. This analyzed data or information will change our business and daily life. Big possibilities come for analyzing the data across the system. For this, we need a better storage so that we can store a large amount of data easily & retrieve the data without any error. So in this paper we have discussed the technique for converting the information in 2.14*10^6 bytes in DNA oligos.